OzoNews Volume XIX - 15 February 2019 - United Nations Environment Programme (2019)
In this issue: 1. Scientific Assessment of Ozone Depletion 2018: Full Report Now Available. 2. Study provides more evidence of the recovering Antarctic ozone hole. 3. ASHRAE/UNEP Lower-GWP Refrigeration and Air Conditioning Innovation Award. 4. Women in science for ozone protection. 5. Rwanda’s ambitious plan for clean and efficient cooling. 6. Effects of climate change felt in Zimbabwe - MPs urged to take lead in finding solutions. 7. Protecting the ozone: Jamaica’s refrigeration industry. 8. Cutting HFCs and other SLCPs is a top sustainable business trend for 2019 - Report. 9. Permit to pollute withdrawn after North Carolina community pushes back 10. UK to support nitrogen research in India. 11. Oman ratified international conventions on the mitigation of the effects of manufactured chemicals. 12. UN, Turkmenistan implementing joint project to reduce ozone-depleting substances. 13. 'Europe's first' professional school for HVAC&R technicians has opened in greater Milan, Italy. 14. Alternative refrigerants e-learning platform is now live in 15 languages. 15. Swedish treatment operators for cooling and freezing appliances are required to comply with the CENELEC EN50625-series.